Outcomes of elective induction of labour compared with expectant management: population based study - Stock, Sarah J (BMJ Publishing Group Ltd., 2012)
Objective To determine neonatal outcomes (perinatal mortality and special care unit admission) and maternal outcomes (mode of delivery, delivery complications) of elective induction of labour compared with expectant management. Design Retrospective cohort study using an unselected population database. Setting Consultant and midwife led obstetric units in Scotland 1981-2007. Participants 1 271 549 women with singleton pregnancies of 37 weeks or more gestation. Interventions Outcomes of elective induction of labour (induction of labour with no recognised medical indication) at 37, 38, 39, 40, and 41 weeks’ gestation compared with those of expectant management (continuation of pregnancy to either spontaneous labour, induction of labour or caesarean section at a later gestation). Main outcome measures Extended perinatal mortality, mode of delivery, postpartum haemorrhage, obstetric anal sphincter injury, and admission to a neonatal or special care baby unit. Outcomes were adjusted for age at delivery, parity, year of birth, birth weight, deprivation category, and, where appropriate, mode of delivery. Results At each gestation between 37 and 41 completed weeks, elective induction of labour was associated with a decreased odds of perinatal mortality compared with expectant management (at 40 weeks’ gestation 0.08% (37/44 764) in the induction of labour group versus 0.18% (627/350 643) in the expectant management group; adjusted odds ratio 0.39, 99% confidence interval 0.24 to 0.63), without a reduction in the odds of spontaneous vertex delivery (at 40 weeks’ gestation 79.9% (35 775/44 778) in the induction of labour group versus 73.7% (258 665/350 791) in the expectant management group; adjusted odds ratio 1.26, 1.22 to 1.31). Admission to a neonatal unit was, however, increased in association with elective induction of labour at all gestations before 41 weeks (at 40 weeks’ gestation 8.0% (3605/44 778) in the induction of labour group compared with 7.3% (25 572/350 791) in the expectant management group; adjusted odds ratio 1.14, 1.09 to 1.20). Conclusion Although residual confounding may remain, our findings indicate that elective induction of labour at term gestation can reduce perinatal mortality in developed countries without increasing the risk of operative delivery.